2015
DOI: 10.1186/s40780-015-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the efficacy and safety of Ginkgo biloba extract for the treatment of dementia

Abstract: BackgroundThe benefit of Ginkgo biloba for the treatment of dementia remains controversial. The aim of this study was to evaluate the efficacy and safety of Ginkgo biloba in patients with dementia in whom administration effects were reported using meta-analysis.MethodsWe searched MEDLINE, Embase, the Cochrane databases, and Ichushi for controlled trials of Ginkgo biloba for the treatment dementia. Clinical characteristics and outcomes were extracted. Meta-analysis results were expressed as standard mean differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 30 publications
2
60
0
1
Order By: Relevance
“…A 2015 meta‐analysis by Hashiguchi et al also demonstrated efficacy results (Syndrome Kurztest [SKT] scores) in favor of EGb 761 ® , both in the AD and AD + VaD subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…A 2015 meta‐analysis by Hashiguchi et al also demonstrated efficacy results (Syndrome Kurztest [SKT] scores) in favor of EGb 761 ® , both in the AD and AD + VaD subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…Investigation on use of Ginkgo biloba extracts EGb761 outperformed in enhancing the cognitive function (Hashiguchi et al, 2015). A randomized clinical trial for huperzine A, which is a sesquiterpene alkaloid separated from Huperzia serrata exhibited potent acetylcholinesterase inhibiting activity (Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a rigorous meta-analysis, 240 mg/day of Ginkgo biloba extract was found to be effective and safe in the treatment of dementia. 58 Bacopa monnieri , otherwise known as water hyssop, also has evidence from a meta-analysis demonstrating improved cognition, especially speed of attention. 59 Omega-3 fatty acid therapy has positive but conflicting results on dosage and benefit so more rigorous research is recommended.…”
Section: Dementiamentioning
confidence: 99%